Renewal of Electrical Installations at Al Falah Mushola Pondok Benda : Perbaikan Instalasi Listrik Di Mushola Al Falah Pondok Benda - Abdul Hakim, Fikri; Abdul Rozak, Ojak; Kusnadi, Heri; Supriadi , Oky; Agus Ardianto, Donie (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
Electrical energy can encourage economic growth and public knowledge. However, electrical energy also has potential safety hazards if it is mishandled and used. We often hear in the mass media that fires occur due to short circuits or accidents caused by being touched by electric currents which cause injuries and even fatalities. This is because the electrical installation installers are not neat, causing electric current leaks and causing sparks and resulting in fires due to the electrical installation not being in accordance with reference standards. One of the efforts to help the government and the community in installing electricity on a household scale (Domestic), is to carry out Community Service activities at the mosque Al Falah which is located at the Al Falah 2 RT. 005 RW. 009, Pondok Benda, Pamulang, South Tangerang. The method used in this Community Service activity is to invite the community to come to the location where electrical installation repairs will be carried out. This is done so that people know how to install electricity and immediately practice it. The tools and materials that will be used to check and repair electrical installations at the mosque Al Falah include multimeters, test pens, current limiters, fuses, cables, insulation testers, conduit pipes and electrical insulation. The result of this Community Service activity is that the electrical installation at the mosque Al Falah becomes suitable for use in accordance with PUIL 2000.